Snake bites with Neuropsychiatric Presentation ─ A Study in Hill Tracts of Bangladesh (Journal of Enam Medical College, 2018)
Background: Snake bite is a common medical emergency and one of the important causes of mortality and morbidity in hill tracts of Bangladesh. Neurological and psychiatric features predominate as both early and late features of snake bite patients and need to be identified correctly for proper management.Objective: The aim of this study was to find out the pattern of early and late neuropsychiatric manifestations of snake bite in hill tracts with clinical outcomes.Materials and Methods: This descriptive hospital-based study was done on 121 snake bite patients during the period from January 2015 to July 2016 using simple, direct, standardized questionnaire with history, neurological examination and psychiatric evaluation.Results: Majority of cases (71.9%) were admitted into hospital after two hours of snake bite. Lower limb was the commonest site (75.2%) of bite. Generalized weakness (50.4%) and anxiety (52.9%) were the commonest early neurological and psychiatric manifestations. Numbness (57%) and depression (33.9%) were the commonest late neurological and psychiatric manifestations among survivors; 37.2% needed referral to tertiary care hospital and 34.7% received antivenom. Death rate was 17.4% and 73.6% were cured completely without complication.Conclusion: As neurological and psychiatric manifestations are common in both early and late stages in snake bite in hill tracts, these are to be considered in the total management to decrease mortality and morbidity.J Enam Med Col 2018; 8(1): 20-24